2016
DOI: 10.1007/s12079-016-0320-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Wnt and NOTCH pathways in esophageal squamous cell carcinoma

Abstract: There is an inevitable association between cell signaling pathways and tumorigenesis. Wnt and notch pathways play important roles during development and self-renewal. Beside the independent role of such pathways on tumor progression, different cross talks between these pathways through tumorigenesis are emphasized. In this study, we analyzed cross talk between Wnt and NOTCH signaling pathways through assessment of probable correlation between MAML1 and PYGO2 as the main transcription factors of these pathways,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…The present study was in line with our previous projects about EGFR and MSI1 in ESCC patients to find a probable correlation between these markers and introduce a panel of diagnostic markers [14, 25, 26, 2830]. We have recently reported a direct correlation between PYGO2, the main transcription factor of the WNT pathway, and EGFR, one of the target genes in the WNT pathway [25].…”
Section: Discussionsupporting
confidence: 87%
“…The present study was in line with our previous projects about EGFR and MSI1 in ESCC patients to find a probable correlation between these markers and introduce a panel of diagnostic markers [14, 25, 26, 2830]. We have recently reported a direct correlation between PYGO2, the main transcription factor of the WNT pathway, and EGFR, one of the target genes in the WNT pathway [25].…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, 20.11% of reverse-of-regulation DRLs had the most significant GO terms, and they were enriched in both positive and negative regulation of bio-synthetic and metabolic process and transcription, suggesting their capacity of bi-directional regulation. The KEGG pathway enrichment analysis revealed that the reverse-of-regulation DRLs significantly enriched in Wnt signaling pathway, which was proved to be associated with the ESCC progression and metastasis 33,4547. Our results demonstrated that the alterations of gene-to-gene relationships in the ESCC may be mediated by the dysregulation of TFs to some extent.…”
Section: Resultsmentioning
confidence: 61%
“…Moreover, DIDO1 as a negative mediator also participate in down regulation of NANOG through the KCTD12. In the case of EGFR, we have previously reported that the EGFR as one of the WNT target genes has a positive feedback with b-catenin through stabilization of b-catenin and its translocation into the nucleus [ 7 , 8 , 34 ]. This study also assessed the probable role of KCTD12 in cell motility and data showed that this factor can decrease the cell movement which can be related to the TWIST1.…”
Section: Discussionmentioning
confidence: 99%